Cognitive mechanisms and neurological foundations of companion animals’ role in enhancing human psychological well-being - Liu, Heng; Lin, Jingyuan; Lin, Wuji (Frontiers in Psychology, 2024)
The impact of companion animals on human psychological health has garnered widespread attention. Research demonstrates that companion animals contribute positively in various ways, including reducing depression, anxiety, stress, and fostering positive emotions in humans. Recent studies have revealed significant changes in the activity levels of human emotion-related cortical areas (such as the frontal cortex and amygdala) and neurotransmitter (e.g., oxytocin, cortisol) secretion due to interaction with companion animals. However, research in this domain is still in a nascent stage, with many unknowns in the cognitive neural mechanisms involved. This paper proposes that to understand the cognitive mechanisms through which companion animals affect human psychological health, we need to examine changes in emotional cognitive processing. It aims to uncover the neurological underpinnings of how companion animals enhance human psychological well-being from the perspective of brain connectivity. This approach is expected to provide theoretical support and direction for future research and practical applications in this field.